en - NI WAYAN SUNARIASIH; Putu Lirisathi Soetama (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2023)
The objective of this research is to find out and analyze the types of conversational implicature and its function used by Selena Gomez in Zach Song Show’s interview on 2016 discussing about her new song and mental health issues. The method used to conduct this research is descriptive qualitative method. This study used the theory of cooperative principle by Grice and the function of implicature by Levinson. There are two types of conversational implicature occured in the interview; those are generalized conversational implicature and particularized conversational implicature. This study also found that Selena Gomez mostly use the implicature in order to obtain two functions namely ability to obtain a functional explanation that is important to language realization but is not covered by descriptive and providing a firm and explicit explanation about the possibility that language users can grasp messages even when what is spoken differs from what is meant.